Case Report: Intestinal metastasis from ALK-rearranged pulmonary pleomorphic carcinomas mimicking inflammatory myofibroblastic tumors - Shi, Changle; Qiu, Yan; He, Kang; Li, Yuli; Wan, Qingsong; Yao, Jin; Zhang, Hongying (Frontiers in Oncology, 2025)
Lung carcinomas usually spread to the liver, lungs, pleura, pericardium, adrenal glands, brain, and bones. Anaplastic lymphoma kinase gene (ALK) fusion occurs in approximately 5% of non-small cell lung cancer (NSCLC) cases and most frequently in adenocarcinoma. Here, we report a rare case of intestinal metastasis originating from pulmonary pleomorphic carcinoma in a 49-year-old male heavy smoker. At the local hospital, the patient was initially considered to have an ALK-positive intestinal tumor, leading to a differential diagnosis of inflammatory myofibroblastic tumor (IMT). Due to the tumor’s peculiar morphology (including epithelioid and spindle cell components), pathologists of the local hospital sent slides of the case to our hospital for further consultation. Immunohistochemical analysis revealed that the epithelioid and spindle neoplastic cells were positive for CK7, TTF1, and ALK-V. Fluorescence in situ hybridization (FISH) confirmed the presence of the echinoderm microtubule-associated protein-like 4 (EML4):: ALK fusion. Based on these findings, we established the final diagnosis as intestinal metastasis of ALK-positive pulmonary pleomorphic carcinoma. A subsequent enhanced CT scan of the chest revealed a 3.0 cm solid mass in the right upper lung, further supporting the diagnosis of intestinal metastasis originating from pulmonary pleomorphic carcinoma. In conclusion, this case exhibited highly unusual clinicopathological features that could easily lead to misdiagnosis as primary intestinal tumors with ALK rearrangement. Pathologists must know this possibility to ensure accurate diagnosis and appropriate management.